Invasive Pulmonary Aspergillosis: case report in a reference hospital in Piura - Farfán-Chávez, Luis Gabriel (2024)
Introduction: Invasive pulmonary aspergillosis is a severe fungal infection caused by Aspergillus species. Case report: A 61-year-old male presented to the emergency department of a tertiary hospital in Piura with acute respiratory failure. He was admitted with a diagnosis of complicated pneumonia, with differential diagnoses including pulmonary abscess, pulmonary tuberculosis, and malignancy. However, during his hospital stay, rapid progression on pulmonary imaging combined with a positive galactomannan result in bronchoalveolar lavage led to the diagnosis of invasive pulmonary aspergillosis (IPA), which responded well to antifungal treatment. Conclusion: Early identification and a multidisciplinary approach are key to improving the management and prognosis of invasive pulmonary aspergillosis.